PENGARUH LAMA PENYIMPANAN JAMUR Metarhizium anisopliae TERHADAP MORTALITAS ULAT GRAYAK (Spodoptera litura F.) DI LABORATORIUM - Dewi Hastuti; Tubagus Bahtiar Rusbana; Djamaludin Noor Hidayatullah (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2017)
This research was aimed to know the effectiveness level of different storage time of the fungus Metarhizium anisopliae to armyworm at Laboratory. The research was conducted at BPTPH Region 1 Banten as a repository of biological agents Metarhizium anisopliae and Soil & Agroklimat Laboratory of Agriculture Faculty, Untirta. This research was carried out from October 2015 until February 2016. Environmental design used Randomized Block Design non factorial, with the treatment was storage time of biological agents Metharizium anispoliae that have three levels, i.e. the storage time for 1, 2 and 3 months. Four testing trials include mortality, LT50 test, conidia test, test the intensity of the attacked and describe the morphology of the fungus-infected larvae Metharizium anisopliae. These results showed that the storage time was highly significant in the mortality of Spodoptera litura Fabricius larvae. Provision storage 1 month-long treatment was the best treatment to kill the larvae of Spodoptera litura Fabricius were infected Metharizium anisopliae fungus than the treatment for 2 and 3 months of storage. In the mortality test, LT50 test and intensity test of attacked larvae of Spodoptera litura Fabricius treatment 1 month storage time showed the best results compared to other treatments. The test of conidia density, treatment of storage time 1 month gave showed the highest.Keywords: Spodoptera litura F., Metharizium anisopliae fungus, Larvae mortality